Colour reduction and anti-microbial evaluation of pre-treated cashew leaves extract - Abdul Gaffar, R.; Sazali, N. E. S.; Abdul Majid, F. A. (Faculty of Chemical Engineering & Natural Resources, 2008)
Cashew leaves are used traditionally for various health promoting effects includingj wound healing and diarrhea and could be orally consumed for its effectiveness. Previous research shows that cashew leaves and its bark extracts is rich in tannin and is a potential antimicrobial agent. Extended from these properties, we selected cashew leaves extract as a candidate for potential natural preservative. The extraction method especially using ethanol or other solvent extraction will result in intense colour that will limit its application. The intense green colour of the leaves is due to chlorophyll and become a problem to end product. Various treatments could be used to reduce chlorophyll in the leaves. This study focused on the pretreatment of the cashew leaves in order to minimize the green colour intensity of the extract. Our study shows that pretreatment 3 reduced the green colour intensity significantly. Pretreatment 3: cashew leaves heated in boiling water for 1 minute, immediately cooled in ice-cold water then blotted to dry. The dried leaves then cut into small pieces and floated on the surface of 0.05 M EDTA-2Na, pH 7.0 for 24 hours exposure to the light (5000 lux). The antimicrobial activity of all the extracts was almost similar and was shown to be as effective as methylpareban at concentration as low as 2.5g (v/v). The extract could control the growth of all five main microorganisms as recommended by FDA for cosmetic and bodycare products.